Additional donepezil treatment for patients with geriatric depression who exhibit cognitive deficit during treatment for depression. Issue 1 (27th April 2015) - Inoue, Jun; Hoshino, Ryoichi; Nojima, Hidenori; Ishida, Wataru; Okamoto, Norio
Abstract: Background: Depression is a frequent comorbid condition in patients with Alzheimer's disease (AD). In the present study, we reported the effect of additional donepezil treatment for patients with geriatric depression who exhibited cognitive deficit and were diagnosed with AD during treatment for depression. Methods: The present retrospective study investigated 14 AD outpatients who were diagnosed with geriatric depression at first and received antidepressant treatment. When apparent cognitive decline was observed, all of them were diagnosed with AD and received donepezil (5 mg/day) for at least 1 year. All patients underwent periodic examination of cognitive function (Mini‐Mental State Examination, Rorschach Cognitive Index) and clinical evaluation (Clinical Dementia Rating). The 14 patients were classified into three groups according to their treatment course: (i) 'A' group, patients who showed cognitive impairment during a long course of treatment for depression; (ii) 'B' group, patients who showed cognitive impairment at an early stage of treatment for depression and started to take additional donepezil at least 20 months after the first examination; and (iii) 'C' group, patients who showed cognitive impairment at an early stage of treatment for depression and began taking additional donepezil within 10 months of the first examination. The clinical feature and treatment effects were examined for each group. Results: At 1 and 2 years after the start of treatment, the proportion of patients who had improved or maintained their Clinical Dementia Rating score was higher in 'A' and 'C' groups than in 'B' group. In 'B' group, additional donepezil treatment commenced later than in the other groups. Therefore, donepezil had an insufficient curative effect. Conclusion: The results of this study suggested that early induction of donepezil treatment was necessary when apparent cognitive decline was identified during the treatment of geriatric depression.